Modeling of aerodynamics and heat-and-mass transfer on ventilation of industrial enclosures - Gubanov, S. M. (Atomic energy)
Modeling of the aerodynamic processes involved in the ventilation of a large production enclosure containing electrical equipment requiring special conditions for air humidity and temperature was performed. A physical-mathematical model of the aerodynamics of ventilation of a production enclosure is presented, taking into account heat exchange with air and the surface of the equipment present in a building and mass exchange with the ambient environment by air filtration through the structural elements. The computational results for non-stationary displacement of air with high humidity from the building by means of ventilation with dried air are presented. The characteristic time of purification of air from excess moisture with air supplied to various parts of a building was determined.